FGF23 gene regulation by 1,25-dihydroxyvitamin D: Opposing effects in adipocytes and osteocytes - Kaneko, Ichiro (J Endocrinol, 2015)
In a closed endocrine loop, 1,25-dihydroxyvitamin D(3) (1,25D) induces the expression of fibroblast growth factor-23 (FGF23) in bone, with the phosphaturic peptide in turn acting at kidney to feedback repress CYP27B1 and induce CYP24A1 to limit the levels of 1,25D. In 3T3-L1 differentiated adipocytes, 1,25D represses FGF23 and leptin expression, while not affecting leptin receptor transcription, but inducing C/EBP. Conversely, in UMR-106 osteoblast-like cells, FGF23 mRNA concentrations are upregulated by 1,25D, an effect that is blunted by lysophosphatidic acid, a cell-surface acting ligand. Progressive truncation of the mouse FGF23 proximal promoter linked in luciferase reporter constructs reveals a 1,25D-responsive region between −400 and −200 bp. A 0.6 kb fragment of the mouse FGF23 promoter, linked in a reporter construct, responds to 1,25D with a 4-fold enhancement of transcription in transfected K562 cells. Mutation of either an ETS1 site at −346 bp, or an adjacent candidate VDR/Nurr1-element, in the 0.6 kb reporter construct reduces the transcriptional activity elicited by 1,25D to a level that is not significantly different from a minimal promoter. This composite ETS1-VDR/Nurr1 cis-element may function as a switch between induction (osteocytes) and repression (adipocytes) of FGF23, depending on the cellular setting of transcription factors. Moreover, experiments demonstrate that a 1kb mouse FGF23 promoter-reporter construct, transfected into MC3T3 osteoblast-like cells, responds to high calcium challenge with a statistically significant 1.7–2.0-fold enhancement of transcription. Thus, the FGF23 proximal promoter harbors cis-elements that drive responsiveness to 1,25D and calcium, agents that induce FGF23 to curtail the pathologic consequences of their excess.